141 THE INTENSE PROJECT: IMPROVING DEMENTIA CARE THROUGH SIMULATION OF SELF-EXPERIENCE. (25th October 2022) - Hopper, L; Collins, R; Forristal, K; Riello, M; Conotter, V; Meyer, G; Vugt, M
Abstract: Background: The EC is concerned about the growing shortage of experienced health and social care professionals to care for people with dementia. Although specialized dementia education programs have begun to appear in recent years, a lack of consistency and adequate level of knowledge of dementia to anticipate the required treatment remains across Europe. The Improving demeNtia care Through Self-Experience (INTENSE) project supports the creation of skills improvement paths for professionals across Europe that incorporate and promote successful self-experience methodologies and practices to increase knowledge and understanding of the lived experience of dementia (e.g., Virtual Dementia Tours, role plays and practices of theatre workshops). Methods: A systematic review of self-experience tools, training and interventions was conducted. Participatory stakeholder workshops were then held in Ireland, Italy, Germany and the Netherlands to explore ways in which self-experience could be used to better understand the experience of the person with dementia and how the simulation of self-experience could be incorporated into existing (or new) training programmes. Workshop discussions were transcribed and thematically analysed along with workshop outputs to develop the INTenSE toolkit and supporting platform. Results: An INTenSE toolkit was developed containing interactive no-tech, low-tech and high-tech approaches to simulating self-experience. Training scenarios, facilitation approaches and sustainability plans were designed and a prototype of the INTenSE Platform (website to house and support use of the toolkit) was developed. Beta versions of each will be presented. Conclusion: INTenSE has illustrated how participatory research can strengthen cooperation and exchange of experiences between organizations working in the field of dementia care; improve social awareness of the ability of self-experience to improve dementia care; promote the integration of self-experience practices in the training of health and social care professional; and highlight the potential for self-experience simulation to be incorporated into carer training and dementia awareness education, subject to the provision of appropriate supports.